Psychological Capital and Work Engagement: The Moderating Role of Age Diversity - Alice S.M. Gleichmann; Arum Etikariena (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
Work engagement to private sector workers during the Covid-19 pandemic has been stationary or experienced a decline. One of the antecedents of work engagement is personal resources construct. One derives personal resources construct is psychological capital based on the Job Demand Resources (JD- R) model. This research aims to prove the moderating role of age diversity to private sector workers in connection between psychological capital and work engagement referring to the theory of “Conservation of Resource” (COR). This research involves 127 Jabodetabek employees that works in private sectors. The measuring instrument used is Utrecht Work Engagement scale (UWES)-9, Psychological Capital Questionaire (PCQ-24) and age diversity that is categorized in 4 groups. The result of the research shows that there is a significant positive connection between psychological capital and work engagement of private sector employees. In other side, age diversity does not have a moderation effect, there is insignificant interaction effect between psychological capital and age diversity to work engagement, who the majority of participants in this study have already led to the stage of maintaining (age 41- 60 years old). With regard to the second most participants entering the advancement stage (ages 27–40 years old). In addition, this research proves employee who has high psychological capital; resulting in an increase of work engagement